Keterlibatan Perempuan dalam Organisasi Teroris Boko Haram di Nigeria - Maharani, Farah (Global and Policy Journal of International Relations, 2022)
ABSTRACTBoko Haram is an Islamic extremist organization that believes that politics in Northern Nigeria hasbeen taken over by fake Muslim groups (Walker, 2012). This organization makes women both asagents of combatants as well as victims of violence and harassment. The Boko Haram case thatattracted international attention was the kidnapping of 276 female students in Chibok City on April14, 2014 (BBC, 2016). Therefore, the author formulates this research problem by discussing thebasic question, namely How is the involvement of women in the Boko Haram terrorist organizationin Northern Nigeria? This research is qualitative and descriptive. By using secondary data sourcessuch as books, journals, news articles, and other sources. Boko Haram implements a genderterrorist strategy by using women as sex slaves, human shields, weapons couriers, and sources ofransom. Where Boko Haram has justified gender-based violence as a terror strategy. Nigeria'scurrent strategy for dealing with terrorism has been adapted to emphasize gender sensitiverehabilitation and reintegration processes. This effort is intended for those involved with violentextremist organizations as both victims and perpetrators.Keywords: Terrorism, Boko Haram, Gender, Women, Nigeria, Counter-terorrismDOI: https://doi.org/10.33005/jgp.v10i01.3572